Ozone (O3) and sono (US) based advanced oxidation processes for the removal of color, COD and determination of electrical energy from landfill leachate - Asaithambi, P.; Sajjadi, B.; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan (Elsevier, 2017)
In this study, the removal of color and COD from landfill leachate, together with the electrical energy per order by the ozonation (O3), sonication (US), O3/H2O2, US/H2O2, O3/Fe2+/H2O2, US/Fe2+/H2O2 and O3/US/Fe2+/H2O2 processes was studied. The experimental results indicated that the color removal, COD removal and electrical energy per order from the landfill leachate were 100%, 95%, and 1.20 kW h/m3, respectively, at the optimum operating conditions. The obtained values were much higher than that obtained in the O3 and US based advanced oxidation processes. The effects of various experimental parameters such as Fe2+ concentration, H2O2 concentration, solution pH, COD concentration, ozone production and sonication power were studied to identify the optimum conditions leading to maximum removal of color and COD with minimum electrical energy per order by the O3/US/Fe2+/H2O2 process. The synergy index between the O3 and US/Fe2+/H2O2 processes was studied and reported. The results indicated that the combination of O3 and US based advanced oxidation processes could effectively treat the industrial effluents and wastewater.